Efficient removal of manganese from water using bentonite and zeolite adsorbents: A study on natural resources from Aceh, Indonesia - Mulyati Sri; Suraiya; Hafidhah Bunga; Rahmatillah Rifda; Ambarita Aulia Chintia; Az-harry Muhammad (BIO Web of Conferences)
Excessive levels of manganese in drinking water pose serious health risks and environmental concerns. This study investigates the efficacy of natural bentonite and zeolite, which are abundant in Aceh, Indonesia, as adsorbents for manganese removal. Adsorption experiments using activated bentonite and zeolite were conducted to study the effects of various parameters on adsorption efficiency. The results showed a removal efficiency of 98% at 60 min contact time and 1 g/L adsorbent dosage. The optimum adsorbent ratio of 1:1 gave an efficiency of 97.134%. The Langmuir and Freundlich models were used to evaluate the adsorption isotherms, with the Langmuir model showing a better fit and indicating monolayer adsorption. This study highlights the potential of natural bentonite and zeolite from Aceh as effective and economical adsorbents for manganese removal, providing a sustainable water treatment solution.